Surviving node-node failures within wireless networks for a near optimal ant colony system message re-routing. (8th June 2020) - Owoade, Ayoade Akeem; Osunmakinde, Isaac Olusegun
This research develops the ant colony system (ACS) survivability model based on capacity efficiency and fast restoration to swiftly resolve node-node failure problems for increasing quality of service. The resilience of the swarm model was tested on such failures at different locations on 20, 26 and 30 node wireless networks. The proposed ACS-based capacity efficiency model was able to generate near optimal paths, the bandwidth required for fast rerouting, the transmission delay and the transmission time for re-routing voice messages. Increased multiple node failures revealed that transmission delay is high when insufficient bandwidth is used for message transmission. Further experiments revealed that the higher the number of nodes on the network, the higher the bandwidth required to transmit a message effectively. Hence, the ACS-based capacity efficiency model therefore outperforms the Dijkstra algorithm, adaptive and reactive restoration models in terms of speed of transmission, transmission delay and running time complexity. The new solution paths generated from these experiments demonstrated that the proposed swarm technology is feasible for current business applications that require high speed/broadband networks.